2002
DOI: 10.1002/app.11212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the actual diameters and diameter ratios of barrels and dies on the elastic swell and entrance pressure drop of natural rubber in capillary die flow

Abstract: ABSTRACT:The effects of the actual diameters and diameter ratios of barrels and dies on the elastic swell and entrance pressure drop of natural rubber compounds in an extrusion capillary rheometer were investigated. Either the barrel diameter or the die diameter was altered so that diameter was fixed, the relationship between the entrance pressure drop and the extrudate swell was linear up to a certain value of the barrel diameter greater than 30 mm. Beyond this critical barrel value, the relationship became n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…In addition, the presence of agglomerates (due to high filler load) caused resistance against the flow and increased viscosity of composites. All the dynamic viscosity decreases showing shear thinning behavior as previously observed in other filler melts [46] [47]. This behavior can be attributed to the higher degree of polymer-filler interaction, which requires higher shear stress and longer relaxation times for the composites to flow [48].…”
Section: Rheological Behaviorsupporting
confidence: 69%
“…In addition, the presence of agglomerates (due to high filler load) caused resistance against the flow and increased viscosity of composites. All the dynamic viscosity decreases showing shear thinning behavior as previously observed in other filler melts [46] [47]. This behavior can be attributed to the higher degree of polymer-filler interaction, which requires higher shear stress and longer relaxation times for the composites to flow [48].…”
Section: Rheological Behaviorsupporting
confidence: 69%
“…The change in extrudate swell was found to be associated with the degree of flow complexities in the barrel, residence time, elastic characteristic and the temperature rise. They also found that the change in extrudate swell was linearly influenced by entrance pressure drop at low actual barrel/die diameters (D B /D D from 20/4 to 30/7 mm/mm), but was associated with the change in material viscosity at high actual barrel/die diameters (D B /D D from 35/ 7 to 40/8 mm/mm) [6]. For a constant barrel diameter, the smaller the die diameter the greater the extrudate swell due to the increases in the extensional deformation, shear rate, and a reduction in the melt residence time.…”
Section: Introductionmentioning
confidence: 97%
“…[5,6] So, there exists a critical value of die length above which reduction of the die length would not have much effect on the die swell ratio but could dramatically reduce the extrusion pressure while the flow rate remains constant or increase the flow rate while the extrusion pressure remains constant. We suggest this critical length is the entrance length.…”
Section: Entrance Length Of Polymer Flow Through a Contraction Die 947mentioning
confidence: 99%